Etiology of biliary atresia as a developmental anomaly: recent advances. Issue 5 (June 2013) - Nakamura, Kazuaki; Tanoue, Akito
Abstract Biliary atresia (BA) is a progressive fibro‐obliterative cholangiopathy affecting the extra‐ and intrahepatic biliary tree to various degrees and resulting in obstructive bile flow, cholestasis and icterus in neonates. It is the most common cause of pediatric liver transplantation. The etiology of BA is still unclear, although there is some evidence pointing to viral, toxic, and multiple genetic factors. For new therapeutic options other than liver transplantation to be developed, a greater understanding of the pathogenesis of BA is indispensable. The fact that the pathology of BA develops during a period of biliary growth and remodeling suggests an involvement of developmental anomalies. Recent studies indicate an association of the etiology of BA with some genetic factors such as laterality genes, epigenetic regulation and/or microRNA function. In this paper, we present an overview of recent advances in the understanding of the disease focusing on bile duct developmental anomaly.